The Idea of the city. - University-at-Large Programs, inc.; Association-Sterling Films (University-at-Large, Released by Association-Sterling Films, 1968)
John Kenneth Galbraith traces the history of the modern city from its preindustrial state to the present, and examines the economic, aesthetic, and political needs of the industrial city, and considers its failures with particular minority groups. Discusses the concept of the responsibility of the city for its inhabitants and outlines a new role for urban government.
Producer and director, David X. Young.
Keywords: Galbraith, John Kenneth, -- 1908-; Cities and towns; Municipal government